Experiences of Critical Care Units Nurses about Futile Care a Qualitative Study - Leili Yekefalah; Tahere Ashktorab; Homan manouchehri (Zanjan University of Medical Sciences and Health Services, 2015)
Background and Objectives: The concept and meaning of futile care depends on the existing culture, values, religion, beliefs, medical achievements and emotional status of a country. We aimed to elaborate the concept of futile care from view points of nurses working in critical care units in Iran. Materials and Methods: The participants of this phenomenological study included 25 nurses working in the ICUs. Face-to-face interviews and observations were used to collect data. All interviews were recorded and codes and themes were extracted using the Van Manenchr('39')s analysis method. Results: Initially, 191 codes were extracted. During data analysis and comparisons, the codes were reduced to 178 ones. Ultimately, nine sub-themes and four themes were emerged. The participants defined the futile care as: "useless and ineffective care that wastes resources and irritates and annoys the patients and nurse and includes Nursing and medical aspects". Conclusion: Regarding key role of nurses in managing futile care, being aware of their experiences in this regard could be the initial step for providing useful care and delivering educational programs in ICUs.